2001
DOI: 10.1139/z01-130
|View full text |Cite
|
Sign up to set email alerts
|

Densities of breeding birds and changes in vegetation in an Alaskan boreal forest following a massive disturbance by spruce beetles

Abstract: We examined bird and plant communities among forest stands with different levels of spruce mortality following a large outbreak of spruce beetles (Dendroctonus rufipennis (Kirby)) in the Copper River Basin, Alaska. Spruce beetles avoided stands with black spruce (Picea mariana) and selectively killed larger diameter white spruce (Picea glauca), thereby altering forest structure and increasing the dominance of black spruce in the region. Alders (Alnus sp.) and crowberry (Empetrum nigrum) were more abundant in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 53 publications
2
55
1
Order By: Relevance
“…Also, the differences in a mean number of observed bird species and individuals, bird species diversity index (H 0 , Shannon and Weaver 1949), and Simpson's diversity index (D s , Simpson 1949) among study stands were analyzed by simple one-way ANOVA. When the variables were significantly different among stands (P \ 0.05), we used Bonferroni multiple-comparison test to identify specific mean differences (Matsuoka et al 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Also, the differences in a mean number of observed bird species and individuals, bird species diversity index (H 0 , Shannon and Weaver 1949), and Simpson's diversity index (D s , Simpson 1949) among study stands were analyzed by simple one-way ANOVA. When the variables were significantly different among stands (P \ 0.05), we used Bonferroni multiple-comparison test to identify specific mean differences (Matsuoka et al 2001).…”
Section: Methodsmentioning
confidence: 99%
“…overstorey. No studies involving disease-induced loss of overstory are available for comparison, but similar studies on forest insect attack have indicated the importance of canopy, with canopy-dependent species declining due to the loss of habitat (Matsuoka et al, 2001;Rabenold et al, 1998;Tingley et al, 2002).…”
Section: Are Changes In the Bird Community Related To Changes In Habimentioning
confidence: 99%
“…On the Kenai Peninsula as many as 14 species of mammals and 30 species of birds commonly feed on berries (Martin et al, 1951;Erhlich et al, 1988). The spruce beetle infestation changed the forest canopy structure and directly affected habitat use by many forest birds (Lance and Howell, 2000;Matsuoka et al, 2001). Changes in understory vegetation as a result of decreased overstory competition affected habitat used by small mammals (Williams, 1999;Matsuoka et al, 2001;Lance et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The spruce beetle infestation changed the forest canopy structure and directly affected habitat use by many forest birds (Lance and Howell, 2000;Matsuoka et al, 2001). Changes in understory vegetation as a result of decreased overstory competition affected habitat used by small mammals (Williams, 1999;Matsuoka et al, 2001;Lance et al, 2006). Similarly, changes in browse availability altered how www.elsevier.com/locate/foreco Forest Ecology and Management 227 (2006) [247][248][249][250][251][252][253][254][255][256] moose used this landscape (Collins and Schwartz, 1998).…”
Section: Introductionmentioning
confidence: 99%